If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 80 = 2(n + 6) Reorder the terms: 80 = 2(6 + n) 80 = (6 * 2 + n * 2) 80 = (12 + 2n) Solving 80 = 12 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 80 + -2n = 12 + 2n + -2n Combine like terms: 2n + -2n = 0 80 + -2n = 12 + 0 80 + -2n = 12 Add '-80' to each side of the equation. 80 + -80 + -2n = 12 + -80 Combine like terms: 80 + -80 = 0 0 + -2n = 12 + -80 -2n = 12 + -80 Combine like terms: 12 + -80 = -68 -2n = -68 Divide each side by '-2'. n = 34 Simplifying n = 34
| -3.3=4.7-4y | | 6/(2a) | | .30=x(.14)+(1-x)(.05) | | 4x-11=15-9x | | -10500x^3+5000=0 | | 6+5z=8+5z | | 102x^2+6y^2+89y-322=0 | | 55x-39x+12=-64 | | -4=-2(5n-2)-8(-7n+1) | | 28-2x=3x+18 | | .03=.14x+.05-05x | | 8+.09m=90 | | G(2)=5-7+2 | | b/0.8=12.6 | | -6m-13=74 | | 6x^2-54x/x-9•7x/6x | | -7.1=2.9-5y | | 10=1.25*p | | g/3.2=4.7 | | g/2=0.5 | | 4r^2=34-10r | | 4(24)=4(20)+4(4) | | (5x+7)+(4x-18)+(3x+2)=x | | 4q+8q+7q-7= | | 9x+x=79 | | 2(6k-7)+6(-3k+1)=22 | | 175+g=118 | | 4y=3(y-5)-2 | | 4(24)=4(20+4(4)) | | 4=0.25(w-4/3) | | 5x+7+4x-18+3x+2=x | | F(2)=5-7+2 |